Evolução molecular dos genes doublesex e fruitless em moscas-das-frutas do grupo Anastrepha fraterculus (Diptera, Tephritidae) - Júnior Sobrinho, Iderval da Silva (2009)
Species of the Anastrepha fraterculus group are one of the most important agricultural pest from South America and form a group of closely related species whose identification is very difficult. It is problematic to establish reciprocal monophyly of species from this group, because of the great variability and superimposition of morphological traits used in their identification. Many evidences suggest that sex-related genes would be good candidates to discriminate species with low divergence, because they could be involved in the speciation of such species and show high level of differentiation rate. Most of such studies are on genes related to male-female interaction, however few are focused on sex-differentiation genes. We originally aimed to study the role of two sex-determination genes, doublesex (dsx) and fruitless (fru), in the differentiation of the species of Anastrepha fraterculus complex. We also studied the molecular evolutionary pattern of these genes, from high divergence interspecific to low divergence intraspecific data. In the process we assessed the hability of different methodologies in detecting signals of particular selective patterns in the studied regions, and tested a new approach to investigate patterns of positive selection using population data. In this new approach we combined in the same analysis synonymous and nonsynonymous mutations frequencies, their position in the haplotype network, and nonsynonymous mutations capacity to change amino acid physicochemical properties. Differently of what was proposed in previous works, both dsx and fru showed distinct signal of positive selection promoting their differentiation. Furthermore, we detected a selective sweep in the fru connecting region of A. obliqua, possibly involved in the split of haplotype network in two groups, with A. obliqua isolated from the other two species. Although both genes are involved in the sex-differentiation cascade, fru established in clearer way the separation, although not yet completely, of A. obliqua from the other two species here studied.